Teaching writing as journey, not destination : essays exploring what "teaching writing" means - Thomas, P. L. 1961- (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
American author Kurt Vonnegut has famously declared that writing is unteachable, yet formal education persists in that task. Teaching Writing as Journey, Not Destination is the culmination of P.L. Thomas's experiences as both a writer and a teacher of writing reaching into the fourth decade of struggling with both.This volume collects essays that examine the enduring and contemporary questions facing writing teachers, including grammar instruction, authentic practices in high-stakes environments, student choice, citation and plagiarism, the five-paragraph essay, grading, and the intersections of being a writer and teaching writing. Thomas offers concrete classroom experiences drawn from teaching high school ELA, first-year composition, and a wide range of undergraduate and graduate courses. Ultimately, however, the essays are a reflection of Thomas's journey and a concession to both writing and teaching writing as journeys without ultimate destinations.